Pengaruh Kesadaran, Lingkungan, dan Sanksi Pajak Terhadap Kepatuhan WPOP dengan Persepsi Fraud Pajak Sebagai Variabel Pemoderasi di KPP Pratama Badung Utara - Ni Made Dwi Putriani; Ida I Dewa Ayu Manik Sastri; I Wayan Kartana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study describes the factors that affect the level of taxpayer compliance. These factors are the awareness of taxpayers, taxpayers' environment, and tax sanctions with the perception of tax fraud as a moderating variable. The population uses WPOP in North Badung Regency. The data in North Badung Pratama KPP, until 2019 there are 69,676 registered WPOPs. The sample was taken by nonprobability sampling method with the technique of incidental sampling. Samples were taken as many as 100 people. Data collection using a questionnaire. Data analysis using moderated regression analysis. The test results have proven that the awareness of the taxpayers, the environment of the taxpayers, and the tax sanctions have a positive effect on the level of taxpayer compliance (sig <Î± = 0.05) and the perception of tax fraud is able to moderate the awareness of taxpayers, the environment of taxpayers, and tax sanctions on the level of compliance of taxpayers.